First fossil jacobsoniid beetle (Coleoptera): Derolathrus groehni n. sp. from Eocene Baltic amber. (28th March 2016) - Cai, Chenyang; Leschen, Richard A. B.; Liu, Ye; Huang, Diying
Abstract: Jacobsoniidae, comprising a small group of small-to-minute polyphagan beetles, is a family presently placed within Derodontiformia. No fossil jacobsoniid has been described to date. Here, we describe the first fossil jacobsoniid, Derolathrus groehni n. sp., based on two well-preserved individuals in middle Eocene Baltic amber. Micro–computed tomography (micro-CT) was used to reveal many diagnostic characters of the Recent genus Derolathrus Sharp. Derolathrus groehni is compared with modern Derolathrus species and is noteworthy for the well-developed eyes and elongate prothorax.